The Environment and the European Public Sphere Perceptions, Actions, Policies - Wenkel, Christian (The White Horse Press, 2023)
Since the 1970s, environmental issues have become a major concern for European citizens and thus for European politicians. In the same time frame the political sphere in Europe, and in particular within the European Union, has also been undergoing major transformations. Dealing with environmental issues over more than fifty years in a historical perspective enables us to gain a better understanding of these transformations, notably the emergence of a European public sphere and how this is changing decision-making processes. Drawing on recent research results from various disciplines, including history, sociology, law and political sciences, this volume addresses the methodological challenge of a European perspective on a transnational subject - one that is commonly distorted by a national prism. It shows how perceptions of the environment are increasingly converging and how these convergences of views across political or linguistic borders in the long run exert an undeniable influence not only on political debates but also on political decisions across Europe. Revealing European characteristics of perceptions, debates and policies, this volume contributes to a history of Europeanisation beyond the usual political turning points and limits.